Global Geo-Informatics Options by Context (GeOC) Flyer - Fradi, Fajr; Diwediga, Badabate; Graziano, Valerio (2017)
This is the french version of the flyer done for the workshop "Systems Tool-aided Participatory Development of Sustainable Land Management Scenarios: 2nd Workshop". This activity is under the output activity "User-friendly, interoperable online tool, containing country-specific, accessible knowledge base of standardized, geo-referenced SLM, to enable stakeholders to query SLM options in different context" of the GIZ funded project 'Impact evaluation of SLM options to achieve land degradation neutrality'.